Does Increasing Climate Model Horizontal Resolution Be Beneficial for the Mediterranean Region?: Multimodel Evaluation Framework for High‐Resolution Model Intercomparison Project. Issue 2 (14th January 2023) - Mishra, Alok Kumar; Jangir, Babita; Strobach, Ehud
Abstract: The Mediterranean region (MR) is one of the climate change hot spots, posing serious threats to society. The insufficient resolution of the global climate models limits their capability to resolve the complex topography over MR, resulting in a large bias in climate variables. This study examines the performance of four Coupled Model Intercomparison Project phase six models from the High‐Resolution Model Intercomparison Project (HighResMIP) in reproducing the Mediterranean climate. A special focus is put on the role of oceanic and atmospheric model horizontal resolution and spread among the models. Various aspects, relevant to air‐sea interactions and precipitation are examined, including the mean, extremes, and associated mechanisms. All HighResMIP models reasonably well capture the large‐scale oceanic and atmospheric characteristics, but there is a sizable model‐to‐model difference. The Hadley Centre Global Environment Model and European Centre for Medium‐Range Weather Forecasts generally perform better than the other models at comparable atmospheric and oceanic horizontal resolutions. A finer oceanic resolution improves the representation not only of oceanic characteristics (i.e., sea surface temperature, SST) but also of the atmospheric processes (wind and precipitation). Likewise, increasing atmospheric model resolution benefits various atmospheric and ocean characteristics. Over some sub‐basins of the Mediterranean Sea, the intensification of surface wind speed results in the deepening of the ocean's mixed layer leading to cooling, indicating negative feedback in Wind‐SST. In contrast, in other regions, the warmer SST results in the intensification of wind (positive feedback in Wind‐SST). Plain Language Summary: This study made an effort to examine the performance of four Coupled Model Intercomparison Project phase six models from the High‐Resolution Model Intercomparison Project for the mean climate and its extremes and associated mechanisms. The Hadley Centre Global Environment Model and European Centre for Medium‐Range Weather Forecasts models generally perform better than the other models at comparable atmospheric and oceanic horizontal resolutions. It is found that, in general, the increasing resolution improves the performance of the model for most of the aspects. Yet, selecting the best‐performing model and tuning the model having unsatisfactory performance is vital. The improvement in the ocean characteristics by increasing atmospheric model resolution and vice versa highlights the importance of fine‐scale air‐sea interaction processes. Key Points: The Hadley Centre Global Environment Model and European Centre for Medium‐Range Weather Forecasts perform better than Euro‐Mediterranean Center on Climate Change and Max Planck Institute Earth System Model at comparable atmospheric and oceanic horizontal resolutions Refinement of oceanic/atmospheric resolution improves the characteristics of the corresponding as well as the other climate components The inter‐model spread and the response to increasing resolution are associated with different feedback processes between sea surface temperature and wind